2012
DOI: 10.1111/j.1600-0765.2012.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits androgen receptor‐mediated collagen production in human gingival fibroblasts

Abstract: IL-1β-induced NO attenuated AR-mediated collagen production in human gingival fibroblasts. The iNOS/NO system down-regulated the axis of AR/Colα1(I) mRNA expression and the production of AR/total collagen proteins by DIGO cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…[30][31][32][33] In addition, P54 nrb /NonO also serves as a repressor of androgen receptor (AR)-regulated gene transcription, and overexpression of P54 nrb /NonO represses AR activity in a dose-dependent fashion, 27 so that androgen-AR-mediated collagen deposition may be similarly enhanced by loss of inhibition caused by P54 nrb / NonO. [34][35][36] Although in earlier studies it appeared that deficiency of P54 nrb /NonO may either suppress or enhance collagen deposition, in our present study decreased P54 nrb /NonO expression and increased collagen deposition were observed in AD aortic tissue; furthermore, there was a negative, statistically significant correlation between levels of P54 nrb /NonO mRNA and the deposition of collagen as well as the degree of fibrosis. The lower the levels of P54 nrb /NonO mRNA, the greater were the amounts of collagen and severe fibrosis observed in the aortic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] In addition, P54 nrb /NonO also serves as a repressor of androgen receptor (AR)-regulated gene transcription, and overexpression of P54 nrb /NonO represses AR activity in a dose-dependent fashion, 27 so that androgen-AR-mediated collagen deposition may be similarly enhanced by loss of inhibition caused by P54 nrb / NonO. [34][35][36] Although in earlier studies it appeared that deficiency of P54 nrb /NonO may either suppress or enhance collagen deposition, in our present study decreased P54 nrb /NonO expression and increased collagen deposition were observed in AD aortic tissue; furthermore, there was a negative, statistically significant correlation between levels of P54 nrb /NonO mRNA and the deposition of collagen as well as the degree of fibrosis. The lower the levels of P54 nrb /NonO mRNA, the greater were the amounts of collagen and severe fibrosis observed in the aortic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…RAW 264.7 macrophages were plated at a density of 2 × 10 5  cells/mL in 24-well plates for 24 h, followed by cotreatment with different concentrations of Br-RUT and lipopolysaccharide (LPS) (100 ng/mL) for 24 h. The amount of nitrite in the samples was detected using the Griess reagent (1% sulfanilamide in 5% phosphoric acid and 0.1% naphthyl ethylenediamine dihydrochloride dihydrochloride in water). Data are reported as the mean ± standard error of the mean (SEM) of three independent determinations [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Ep -Ep/2 = 47.7 mV/αn where Ep -peak potential of compound, mV; Ep/2 -half wave potential of compound, mV; α -the assuming value = 0,539; n -number of electrons [10].…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…1,4-DHP with positively charged groups are used as vectors for DNA delivery inside the cells [9]. Most biological effects of this class of the compounds are usually ascribed to blocking calcium channels, this can lead to multiple biological effects following different intracellular pathways, resulting in weakening of oxidative stress [10].…”
Section: Introductionmentioning
confidence: 99%